TJNPR 2020
DOI: 10.26538/tjnpr/v4i8.8
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Activity Investigations of Extracts of Different Parts of Lumnitzera littorea Voigt

Abstract: Plants are a great source of potentially beneficial chemical compounds. They produce a wide variety of substances that are used for biological functions and for preventing diseases caused by pathogens, fungi and other sources. Traditionally, it has been a common practice to treat microbial infections such as whooping cough, or skin ailments, and inflammations with crude extracts or decoctions derived from plants. However, there has been information of phenolic or flavonoid acting as bioactive substance but non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There have been several reports on the antibacterial properties of compounds isolated from the bark, root and stem of D. indica (Khan et al, 2006;Koysomboon et al, 2006;Rao et al, 2009;Badole et al, 2011). Another more recent report showed that the change in the chemical composition of each extract directly affected its bioactivity and characteristic of bioactive compounds are important in providing access across the cell walls of bacteria (Vittaya et al, 2020). 7).…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports on the antibacterial properties of compounds isolated from the bark, root and stem of D. indica (Khan et al, 2006;Koysomboon et al, 2006;Rao et al, 2009;Badole et al, 2011). Another more recent report showed that the change in the chemical composition of each extract directly affected its bioactivity and characteristic of bioactive compounds are important in providing access across the cell walls of bacteria (Vittaya et al, 2020). 7).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…(Abeysinghe, 2010). More evidence was reported on the methanolic extracts of R. macronata against A. hydrophila and Escherichia coli (Mahmiah et al, 2018) and the methanolic extracts of the Black mangrove (Lumnitzera littorea) on S. agalactiae, A. hydrophila, V. harveyi and V. parahemolyticus (Vittaya et al, 2020). Despite these previous attempts, there is still a need to explore new herbs as alternatives to replace antibiotic uses in aquaculture.…”
Section: Introductionmentioning
confidence: 99%